Exposición a contenidos nocivos y su incidencia en el comportamiento dentro del aula de clases - Zavala Trejo, María Fernanda (2020)
Behavioral problems are common in childhood but when they become a pathology it is necessary to inquire as to what is causing it. The present study addresses the case of an 8 years old boy whose behavior is affecting his performance in the classroom, so it is proposed to establish a relationship between the contents to which the child is being exposed and the problem behavior, for which has the family and teacher support as a source of reliable information and collaborators in the application of behavioral techniques that favor the decrease and consequently the extinction of the aggressive, negative challenging behavior presented by the minor.